Prediksi Harga Emas Dengan Menggunakan Metode Naive Bayes Dalam Investasi Untuk Meminimalisasi Resiko - Rachmat Rifky Miladi; Yulianti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Precious metal gold is one of the profitable assets to invest and can be an option to invest. There are many factors that affect the price of gold, namely fluctuations in the dollar exchange rate, financial crisis, world oil prices, high demand for gold in the market and the world political situation. The Naive Bayes algorithm is able to produce a classification that is used to predict opportunities that will occur in the future. The purpose of using the Naive Bayes Classifier algorithm is to predict the price of gold which can help investors in making decisions to sell or buy gold in the future. The processed gold data is sourced from observations on www.KursDollar.org from 1 to 31 July 2022 as a dataset on the dollar exchange rate and on the website www.harga-emas.org as a gold price dataset. Based on the results of tests that have been carried out up to the cross validation stage, the Naive Bayes Classifier method can be used to predict gold prices with an accuracy, precision and recall level of 100% with the assumption that there will be a decline in gold prices on the next day, August 1, 2022.